Effects of soil grain size and solution chemistry on the transport of biochar nanoparticles - Zhang, Wenke; Meng, Jun; Huang, Yuwei; Sarkar, Binoy; Singh, Bhupinder Pal; Zhou, Xuanwei; Gao, Jian; Teng, Yunpeng; Wang, Hailong; Chen, Wenfu (Frontiers in Environmental Science, 2023)
Biochar nanoparticles (BC-NP) have attracted significant attention because of their unique environmental behavior, some of which could potentially limit large-scale field application of biochar. Accurate prediction of the fate and transportability of BC-NP in soil matrix is the key to evaluating their environmental influence. This study investigated the effects of soil grain size and environmentally relevant solution chemistry, such as ionic strength (cation concentration, 0.1 mM~50 mM; cation type, Na+, and Ca2+), and humic acid (HA; 0~10 mg/L), on the transport behavior of BC-NP via systematic column experiments. The transportability of BC-NP in the soil-packed column decreased with decreasing soil grain size and was inversely proportional to soil clay content. At low cation concentrations (0.1~1.0 mM), a considerable proportion of BC-NP (15.95~67.17%) penetrated the soil columns. Compared with Na+, Ca2+ inhibited the transportability of BC-NP in the soil through a charge shielding effect. With increasing HA concentration, the transportability of BC-NP increased, likely due to an enhanced repulsion force between BC-NP and soil particles. However, at a high HA concentration (10 mg/L), Ca2+ bridging reduced the transportability of BC-NP in the soil. Breakthrough curves of BC-NP were explained by the two-site kinetic retention model. The antagonistic effects of ionic strength and HA indicated that the transport behavior of BC-NP in the soil was governed by competitive effects of some environmental factors, including soil grain size, environmental solution chemistry, and natural organic matter content.